2022
DOI: 10.33395/sinkron.v7i2.11408
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Support Vector Machine Algorithm for Shopee Customer Sentiment Anlysis

Abstract: As the number one largest marketplace in Indonesia based on the criteria for the origin of international stores, Shopee must always improve the quality of its products and services based on reviews from users. Given the huge number of user reviews, it is not effective to identify them by reading one by one. For this reason, an automated system is needed that can read and identify reviews better. Sentiment analysis has proven to do the job. This study aims to conduct a sentiment analysis of shopee product revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…From the five sentiment analysis models tested, the mean of the confusion matrix obtained is precision = 1, recall = 0.97, and f1-score = 0.98. From this study, it can be concluded that the SVM algorithm has been proven to apply to performing sentiment analysis on user reviews of Shopee products with an average accuracy rate of 97.3% (Sitepu, Munthe, & Harahap, 2022).…”
Section: Literature Reviewmentioning
confidence: 90%
“…From the five sentiment analysis models tested, the mean of the confusion matrix obtained is precision = 1, recall = 0.97, and f1-score = 0.98. From this study, it can be concluded that the SVM algorithm has been proven to apply to performing sentiment analysis on user reviews of Shopee products with an average accuracy rate of 97.3% (Sitepu, Munthe, & Harahap, 2022).…”
Section: Literature Reviewmentioning
confidence: 90%
“…First component is pre-processing. Pre-processing is a process to remove unnecessary data contained in the text that does not match the required process (Sitepu, et. al., 2022).…”
Section: Methodsmentioning
confidence: 99%
“…Rahat [11] used the same algorithm as Siswanto and reported that SVM provided higher accuracy (82.48%) than NB. Sitepu [12] utilized the SVM algorithm to analyze customer sentiment on Shopee and found that SVM yielded an accuracy rate of 97.3%. Meanwhile, Xu [13] compared the performance of Linear SVM and Naïve Bayes algorithms for text classification, and SVM was found to be superior based on Precision, Recall, F1-score, and Accuracy metrics.…”
Section: Introductionmentioning
confidence: 99%